The mitochondrial pyruvate carrier mediates high fat diet-induced increases in hepatic TCA cycle capacity - Adam J. Rauckhorst; Lawrence R. Gray; Ryan D. Sheldon; Xiaorong Fu; Alvin D. Pewa; Charlotte R. Feddersen; Adam J. Dupuy; Katherine N. Gibson-Corley; James E. Cox; Shawn C. Burgess; Eric B. Taylor (Elsevier, 2017)
Objective: Excessive hepatic gluconeogenesis is a defining feature of type 2 diabetes (T2D). Most gluconeogenic flux is routed through mitochondria. The mitochondrial pyruvate carrier (MPC) transports pyruvate from the cytosol into the mitochondrial matrix, thereby gating pyruvate-driven gluconeogenesis. Disruption of the hepatocyte MPC attenuates hyperglycemia in mice during high fat diet (HFD)-induced obesity but exerts minimal effects on glycemia in normal chow diet (NCD)-fed conditions. The goal of this investigation was to test whether hepatocyte MPC disruption provides sustained protection from hyperglycemia during long-term HFD and the differential effects of hepatocyte MPC disruption on TCA cycle metabolism in NCD versus HFD conditions. Method: We utilized long-term high fat feeding, serial measurements of postabsorptive blood glucose and metabolomic profiling and 13C-lactate/13C-pyruvate tracing to investigate the contribution of the MPC to hyperglycemia and altered hepatic TCA cycle metabolism during HFD-induced obesity. Results: Hepatocyte MPC disruption resulted in long-term attenuation of hyperglycemia induced by HFD. HFD increased hepatic mitochondrial pyruvate utilization and TCA cycle capacity in an MPC-dependent manner. Furthermore, MPC disruption decreased progression of fibrosis and levels of transcript markers of inflammation. Conclusions: By contributing to chronic hyperglycemia, fibrosis, and TCA cycle expansion, the hepatocyte MPC is a key mediator of the pathophysiology induced in the HFD model of T2D.